2020
DOI: 10.1136/gutjnl-2020-321650
|View full text |Cite
|
Sign up to set email alerts
|

Prioritisation by FIT to mitigate the impact of delays in the 2-week wait colorectal cancer referral pathway during the COVID-19 pandemic: a UK modelling study

Abstract: ObjectiveTo evaluate the impact of faecal immunochemical testing (FIT) prioritisation to mitigate the impact of delays in the colorectal cancer (CRC) urgent diagnostic (2-week-wait (2WW)) pathway consequent from the COVID-19 pandemic.DesignWe modelled the reduction in CRC survival and life years lost resultant from per-patient delays of 2–6 months in the 2WW pathway. We stratified by age group, individual-level benefit in CRC survival versus age-specific nosocomial COVID-19–related fatality per referred patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 22 publications
0
73
0
Order By: Relevance
“…Enhanced vetting of referrals has been used in 77% of recovery plans and has helped to reduce demand. 23 FIT has increasingly been used across the NHS to triage patients for lower gastrointestinal investigation, and recommendations were released in March, 2020, for FIT triaging to be used for patients who were symptomatic in primary care 8 , 24 We show here that FIT could reduce the colonoscopy backlog, if patients with haemoglobin concentrations less than a set FIT threshold are not offered endoscopy. Studies have found that FIT with 10 μg or less haemoglobin per g has a negative predictive value of greater than 99%, with the colorectal cancer risk in patients who are symptomatic similar to the baseline risk.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Enhanced vetting of referrals has been used in 77% of recovery plans and has helped to reduce demand. 23 FIT has increasingly been used across the NHS to triage patients for lower gastrointestinal investigation, and recommendations were released in March, 2020, for FIT triaging to be used for patients who were symptomatic in primary care 8 , 24 We show here that FIT could reduce the colonoscopy backlog, if patients with haemoglobin concentrations less than a set FIT threshold are not offered endoscopy. Studies have found that FIT with 10 μg or less haemoglobin per g has a negative predictive value of greater than 99%, with the colorectal cancer risk in patients who are symptomatic similar to the baseline risk.…”
Section: Discussionmentioning
confidence: 85%
“…Loveday and colleagues suggested that using a FIT cutoff of 10 μg haemoglobin per g could reduce urgent 2-week-wait suspected cancer endoscopies to 18% of usual requirements, if we assume the remaining 82% of patients are not offered endoscopy. 8 NHS England has recommended that a threshold of more than 10 μg haemoglobin per g is used to proceed to colonoscopy, with patients who have concentrations less than the threshold offered safety netting. 10 Data for the proportion of procedures that were on a 2-week-wait pathway was unavailable, but we estimated this proportion using data for indications for colonoscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of FIT10 would allow detection of 80–90% of the cancers in a cohort with the need to urgently colonoscope only 10% of the patients [ 128 , 129 ]. Modelling suggests that use of FIT10 could salvage 90% of the life years lost due to cancer diagnosis delays [ 130 ]. Calprotectin is already established for IBD diagnosis and monitoring [ 131 ].…”
Section: Endoscopic and Other Gi Interventions In Covid-19 Patientsmentioning
confidence: 99%
“…‘Shielding’ is a national measure to protect all those identified as ‘clinically extremely vulnerable’ from COVID-19 through a set of social restrictions including avoiding face-to-face contact, which was especially stringent during the first wave of the pandemic [ 4 ]. Significant alterations in colorectal cancer service delivery with disruptions in the screening and diagnostic pathways, the surveillance endoscopies, as well as in the delivery of radiotherapy systemic treatment to patients with diagnosed colorectal cancer have been reported [ 5 , 6 , 7 ]. Even with the provision of alternative screening tests to mitigate the risks of these unprecedented changes, the impact on the personal lives and psychological wellbeing of patients with cancer is largely unknown.…”
Section: Introductionmentioning
confidence: 99%